Bandoru / Muhamad Alif Danial Mohd Zamri - Mohd Zamri, Muhamad Alif Danial (College of Creative Arts, Universiti Teknologi MARA Kedah Branch, 2022)
Bandoru is a Korean and Japan bundle. The name derived from Korean word "Bandoru" which means bundle in Korea. A quality-checked bundle attire at the lowest rates at Bandoru. You can choose from the wide range of stylish Korean bundle to expand your wardrobe with Bandoru Targeting teenagers and adult around 30-40 years old, Bandoru offered T-shirt, pants, dress, corporate attire and more. Known as Jurangan Bundle before, this company is located at Sungai Petani, Kedah and has been in the market for 7 years. The main uniqueness of this company is a quality-checked bundle attire only from Korea and Japan. The founder claims that bundle items that come from Korea and Japan are very high quality because they only wearing their clothes for 3, 4 days, and put them in a recycling place for clothes. Looking at the design concept, Bandoru comes out with elegant and fresh look style. It is to emphasize that this bundle attire can inspire consumers when wearing it because when our products are high quality it will make consumers comfortable and feel confident. Giving Bandoru a fresh look style, vibrant colors used such as blue, orange and turquois. Nowadays peoples are very concerned about their clothes and their style, yet the economic problem makes them turn into this bundle fashion. People usually think that this bundle attire is a cheap, outdated and this is where Bandoru started to change your mind by making a person look stylish even wearing this bundle attire. Bandoru offers an affordable price, according to the size and type of clothing. Average price is from RM10 until RM50. Finally, Bandoru's vision and mission is to expand their business throughout Malaysia and become the most successful bundle selling company in Malaysia and try out on online platform too.